ANALISIS SEKTOR UNGGULAN PEREKONOMIAN DI KOTA LHOKSEUMAWE, KABUPATEN ACEH UTARA DAN KABUPATEN BIREUEN - Fauzan; neni triana; Reva Rizky Silvana (JAKTABANGUN: Jurnal Akuntansi & Pembangunan, 2022)
This study is intended to identify the characteristics of North Aceh District, Bireuen Regency and Lhokseumawe City as a mainstay area, namely areas that grow fast, have superior sectors, and have economic links with other regions. For this purpose an analytical tool is used: Klassen Tipology, Location Quotient (LQ), Shift Share. The results showed that North Aceh District had a classification of high per capita income and low growth or advanced but depressed regions. With LQ analysis, in almost all sectors in Aceh Regency are the leading sectors except the provision of accommodation and drinking meals. However, the shift share analysis shows that sectors that truly have competitive advantage and specialization have only three sectors, namely the agricultural sector, the government administration sector, the corporate services sector and the service sector. With the classic typology model, it is illustrated that Bireuen District and Lhokseumawe City are two fast-growing but depressed regions, while North Aceh District is a fast-growing and fast-growing region besides that there is a strong link between the three Districts / Cities that can be developed as collaborative partners in area Development. From all the calculations that have been done, a conclusion can be drawn that the determination of North Aceh Regency as a reliable mainstay, however, when viewed from the many leading sectors and the existence of inter-regional economic linkages, North Aceh Regency is considered appropriate.